Giant ovarian cysts: Is a pre- and intraoperative drainage an advisable procedure?. Issue 6 (1st October 2006) - Einenkel, J.; Alexander, H.; Schotte, D.; Stumpp, P.; Horn, L.-C.
Abstract : There has been a considerable debate over the merits of a pre- or intraoperative drainage of giant ovarian cysts, which represented a very frequent approach before definitive surgery in the past. Including our presented case of a 57-year-old woman with a 49 kg mucinous cystadenoma, 19 patients with giant ovarian cysts weighing more than 40 kg were reported in the literature since 1970. An incidence of 37% of malignant and low malignant potential tumors was found. Based on a critical evaluation of the medical courses and the discussed miscellaneous advantages and complications, we conclude that a pre- and intraoperative drainage should be avoided.